2017
DOI: 10.3389/fpls.2017.00108
|View full text |Cite
|
Sign up to set email alerts
|

UFGT: The Key Enzyme Associated with the Petals Variegation in Japanese Apricot

Abstract: Japanese apricot (Prunus mume Sieb.et Zucc.) is an important ornamental plant in China. One of the traits of petals color variegation is attractive, but its formation mechanism is unclear. In our study, RNA-seq technology was employed to characterize the transcriptome response to the mutation of “Fuban Tiaozhi” associated with petals variegation in Japanese apricot. As a result, 4,579,040 (white-flowered, WF) and 7,269,883 (red-flowered, RF) reads were mapped to P. persica genes, while 5,006,676 (WF) and 7,907… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 89 publications
3
45
1
Order By: Relevance
“…From our analysis, the expression patterns of PlANS and PlUFGT are correlated with color intensity, and they showed their highest expression levels in the rose-purple flowers and their lowest in the white flowers. The ANS (Anthocyanidin synthase) encoding enzyme catalyzes the conversion of colorless leucocyanidin into colored anthocyanin [40], and anthocyanin is further glycosylated by different UFGT (UDP flavonoid glucosyl transferase) encoding enzymes that convert the anthocyanidins to different anthocyanin derivatives, exhibiting the final color [41]. We therefore speculate that PlANS and PlUFGT are two crucial genes that determine color intensity in P. limprichtii.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…From our analysis, the expression patterns of PlANS and PlUFGT are correlated with color intensity, and they showed their highest expression levels in the rose-purple flowers and their lowest in the white flowers. The ANS (Anthocyanidin synthase) encoding enzyme catalyzes the conversion of colorless leucocyanidin into colored anthocyanin [40], and anthocyanin is further glycosylated by different UFGT (UDP flavonoid glucosyl transferase) encoding enzymes that convert the anthocyanidins to different anthocyanin derivatives, exhibiting the final color [41]. We therefore speculate that PlANS and PlUFGT are two crucial genes that determine color intensity in P. limprichtii.…”
Section: Discussionmentioning
confidence: 94%
“…We therefore speculate that PlANS and PlUFGT are two crucial genes that determine color intensity in P. limprichtii. It has been revealed that the MBW protein complex, a combination of R2R3-MYB and bHLH transcription factors, along with WD40 proteins, play an important role in regulating the transcription of structural genes [41][42][43][44][45]. The activities of R2R3-MYB factors have distinct roles in determining the action of the complexes, either to promote or inhibit the transcription of anthocyanin biosynthesis genes [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…The color of the flower is an attractive trait, but the underlying mechanism of its appearance is unclear. In addition, it is a central trait of ornamental plants and is determined by plant pigments (Tanaka et al, 2008 andWu et al, 2017). Strong colored petals are valuable in the floricultural market compared to pale colored because they often attract consumer attention.…”
Section: Introductionmentioning
confidence: 99%
“…Each analysis consisted of three biological replicates and three technical replicates of each biorep. The conditions for the PCR amplification were as follows: 95 °C for 3 min, followed by 40 cycles of 95°C for 20 s, 60°C for 20 s, and 72°C for 43 s. The relative expression level of genes and miRNAs wascalculated using the 2 -ΔΔCT method (Wu et al, 2017).…”
Section: Methodsmentioning
confidence: 99%